Correction to: Arctic Micromonas uses protein pools and non-photochemical quenching to cope with temperature restrictions on Photosystem II protein turnover (Photosynthesis Research, (2017), 131, 2, (203-220), 10.1007/s11120-016-0310-6) - Ni, Guangyan; Zimbalatti, Gabrielle; Murphy, Cole D.; Barnett, Audrey B.; Arsenault, Christopher M.; Li, Gang; Cockshutt, Amanda M.; Campbell, Douglas A. (Photosynthesis Research, 2018)
In Table 2 of the original publication, all instances of krec in the Parameter and Equation columns should read krecinact.